ChemInform Abstract: 2, 4‐ and 2, 5‐Disubstituted Arylthiazoles: Rapid Synthesis by C—H Coupling and Biological Evaluation. Issue 6 (23rd January 2015) - Lohrey, Lilia; Uehara, Takahiro N.; Tani, Satoshi; Yamaguchi, Junichiro; Humpf, Hans‐Ulrich; Itami, Kenichiro
Abstract Utilizing common C—H and C—N coupling methodologies, a panel of 2‐arylidenehydrazinyl‐4 (V) and 5‐arylthiazoles (VIII) are synthesized and screened for their biological activity.